2001
DOI: 10.1046/j.1365-4362.2001.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with chemotherapy of scleredema associated with Ig A myeloma

Abstract: A 70‐year‐old woman was referred to the dermatology outpatient clinic in January 1999. During the previous 12 months she had developed a progressive induration and stiffness of the skin of her face, neck, shoulders, and upper aspect of her arms. There was no history of a preceding infection or of diabetes mellitus. An examination revealed that the skin of her face, back, shoulders, arms and chest was shiny, erythematous, and diffusely indurated, with a wooden consistency and decreased range of motion. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Currently there is no established effective treatment for this condition. Various modalities have been tried, including electron beam therapy (3), cyclosporine (4), psoralen plus ultraviolet A (PUVA) (5), low‐dose methotrexate (6), prostaglandin E 1 (7), high‐dose penicillin (8), and chemotherapy in myeloma‐associated scleredema (9), with only limited success. To the best of our knowledge, this is the first report of successful treatment of scleredema with dexamethasone therapy.…”
mentioning
confidence: 99%
“…Currently there is no established effective treatment for this condition. Various modalities have been tried, including electron beam therapy (3), cyclosporine (4), psoralen plus ultraviolet A (PUVA) (5), low‐dose methotrexate (6), prostaglandin E 1 (7), high‐dose penicillin (8), and chemotherapy in myeloma‐associated scleredema (9), with only limited success. To the best of our knowledge, this is the first report of successful treatment of scleredema with dexamethasone therapy.…”
mentioning
confidence: 99%
“…Because scleredema is not uncommonly a benign and asymptomatic condition, its treatment is not always mandatory and we typically have reserved therapy for patients who complains of functional impairment or have systemic implications. In addition, there are prognostic differences between scleredema associated with upper respiratory infection that may heal spontaneously 26 and the other forms of scleredema 27,28 . In our series, three patients had spontaneous resolution, although no history of antecedent respiratory infection was reported; interestingly, one of them had HIV infection that has been anecdotally associated to scleredema 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific association between scleroderma and multiple myeloma has also been explored. The review of literature demonstrated that few articles have reported the cooccurrence of multiple myeloma and scleroderma [ 16 ] or scleroderma-like skin features [ 17 19 ]. Some cases have even experienced improvement of scleroderma symptoms or scleroderma-like skin changes after treatment with chemotherapy for multiple myeloma [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%